Kombinasi Metode AHP dan TOPSIS dalam Pemilihan Bibit Cabai Berdasarkan Kondisi Tanah dan Syarat Tumbuh Tanaman - Nggiri, Maria; Yohanes Malelak (Universitas Boyolali, 2024)
Selecting plant seeds suitable for environmental conditions is crucial for enhancing agricultural productivity. This research aims to develop an effective approach for selecting chili seeds based on plant growth requirements. The Analytic Hierarchy Process (AHP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) methods are employed to address the complexity of multi-criteria decision-making. The first step involves identifying relevant criteria, including soil type, elevation, optimal soil pH, and light intensity. Subsequently, the relative weights of each criterion are determined using the AHP method to consider the significance of each factor in seed selection. Then, utilizing TOPSIS, chili seeds are evaluated based on their relative closeness to the positive ideal solution (seeds with optimal soil conditions and fulfilled plant growth requirements) and the negative ideal solution (seeds with substandard soil conditions and unmet plant growth requirements). The outcome of this research can assist farmers in choosing chili seeds that match soil conditions and plant growth requirements effectively.